Cell‐Penetrating Peptide‐Conjugated BF2‐Oxasmaragdyrins as NIRF Imaging and Photothermal Agents. (28th August 2020) - Laxman, Kandala; Reddy, B. Pradeep K.; Robinson, Andrea; Srivastava, Rohit; Ravikanth, Mangalampalli
Abstract: Cell‐penetrating peptides (CPPs) are excellent cell internalizing agents for hydrophobic drug/dye moieties. We exploited this property of CPPs for the cell internalization of BF2 ‐oxasmaragdyrin by constructing covalent conjugates of BF2 ‐oxasmaragdyrin with CPPs (CRGDK and polyarginine (R9 )) using a solid‐phase peptide synthesis (SPPS) methodology. The CPP‐conjugated BF2 ‐oxasmaragdyrins were purified by reversed‐phase HPLC and characterized by mass spectrometry. The CPP‐conjugated BF2 ‐oxasmaragdyrins were found to be photostable, absorb in the visible‐NIR region (400–700 nm), emit in the NIR−I region (∼715–720 nm) with moderate quantum yields, and be biocompatible, with excellent cellular imaging potential in breast cancer cells (MDA‐MB‐231). The R9 conjugate, being the first water‐soluble BF2 ‐oxasmaragdyrin, also possesses excellent photothermal transduction efficacy with 750 nm laser irradiation and is a potential theranostic agent. Abstract : Green and keen : Synthesized covalent conjugates of BF2 ‐oxasmaragdyrin with cell‐penetrating peptides (CRGDK and polyarginine (R9 )) were photostable, absorb in the visible‐NIR region, emit in NIR‐I region and were successfully used for cellular imaging. The R9 conjugate, being first water‐soluble BF2 ‐oxasmaragdyrin, also possesses excellent photothermal transduction efficacy with 750 nm laser irradiation and is a potential theranostic agent.